The Accuracy of FNAC for Diagnosis of Breast Carcinoma in Gezira State, Central Sudan - Salman, DiaaEldinn Yaseen; ElGaili, ElGaili Mohamed; Khalid, Khalid Eltahir; A., Gamal Mustafa.; Taha, Smai . M. (Gezira Journal of Health Sciences, 2018)
Background : Breast cancer is a leading cause of death in many countries worldwide and breast lesions remain a common diagnostic dilemma. Fine-needle aspiration cytology (FNAC) has been suggested as the most important, first line, minimally invasive procedure in the management of patients with breast lesions. Objective : The aim of this study is to assess the diagnostic efficacy of breast FNAC in patients with breast lesions compared with that of the definitive histological diagnasis. Materials and Methods : This is a hospital-based retrospective study of 112 breast FNAC samples were carried out at Cancer Institute in Medani Gezira state.  FNAC findings were correlated with data from histopathology records to determine the sensitivity and specificity of FNAC. Results: Age group of the patients ranged from 26 to 80 years with mean of 42 years. Among the study subjects (112 case), ductal carcinoma is the common hitological finding 83/88 (94%). According to the cytology, 79% were malignant, 4% were benign and 2% were suspicious. Histological correlation was done in 68 cases. The overall diagnostic accuracy of FNAC was 92.3%, with sensitivity and specificity of 89.2% and 66.5% respectively.  Conclusion: FNAC of breast is asimple, cost effective and less traumatic method for diagnosing breast cancer. It is highly sensitive and accurate, and can reduce the needs for open biopsies. It is recommended that FNAC should be used as a first line method for determining the nature of breast lumps.